Influence of process parameters on the mechanical properties and corrosion resistance of dissimilar friction stir welded joints of AA2024-O and AA6061-O aluminum alloys. (2024)
The influence of the process parameters, traverse, and rotational speeds of dissimilar friction stir welded joints of AA2024-O and AA6061-O aluminum alloys on the corrosion resistance was evaluated. Potentiodynamic tests using a 3.5% NaCl solution, open circuit potential, and polarization curves showed the corrosion behavior for the different welding parameters. These data were correlated with those obtained by mechanical tests (microhardness, tensile, and fracture analysis) and microstructure analysis by optical and scanning electron microscopy. It was observed that the combined effect of the parameters influenced the variation of corrosion resistance. This was evidenced mainly by the improvement of corrosion resistance at 1200 rpm–65 mm·min−1, which was related to the tendency of grain size and heat input presented. The corrosive attacks on the welded joints presented greater affectations in the presence of base material 1 (AA6061-O) with higher metallic dissolution. Corrosion attacks abovementioned were presented in different forms, such as pitting, localized, and selective, and they were observed by scanning electron microscopy. Finally, in corrosive and mechanical terms, the best performing condition was 1200 rpm and 65 mm·min−1 compared to the low parameter of 840 rpm and 45 mm·min−1